Adoption of Mobile Payment Services in Bangalore Urban - A Structural Equation Modelling based Approach - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
The mobile payment adoption in India has not grown at the rate of growth of the mobile phone industry. There is a need to examine the underlying factors among consumers, which influence behavioral intention towards adoption of mobile payments. Six constructs, Perceived ease of use, perceived usefulness, trust, risk, social influence, facilitating conditions are studied to understand attitude and behavioral intention of consumers towards mobile payments adoption. Exploratory factor analysis is conducted on primary responses. The associations between constructs and dependent variables are explored through structural equation modelling. Trust, social influence and perceived usefulness are seen to influence attitude towards adoption. Attitude, trust and perceived risk are seen to have significant associations with behavioral intention towards adoption of mobile payments.